Longitudinal Changes in Refractive Error Among Preschool Children Aged 1–6 Years: The Changsha Children Eye Study - You, Yuxia; Xu, Ming; Song, Yali; Zhou, Huanfen; Wei, Shihui (Frontiers in Medicine, 2022)
Purpose: To investigate the longitudinal changes in refractive error of preschool children and explore the factors related to these changes and the timing of intervention. Methods: The refractive data of preschool children aged 1 to 6 years were collected from 16 community Health Service Centers in Changsha during April 2016 to July 2019 for the retrospective cohort study. The refractive data of each participant was measured with a hand-held vision screener without cycloplegia. A follow-up for all the included participants was performed. The spherical equivalent change was calculated, subsequently, an analysis of risk factors related to the change was performed. Results: 4921 cases were included in the study with the follow-up for 1 to 2 years. The refractive status was found smoothly changed in 67.8% of children. The overall initial SE was 0.62±1.13 D, and the average SE change was -0.20±1.23 D per year. However, profound myopic shift was observed in 32.2% of children. The change of SE in 3-year-old group is most overt. The proportions of 1-6 years old who showed moderate and severe myopic shift (SE change ≥-1.00 D) were 21.6%, 18.9%, 28.2%, 25.5%, 13.4%, and 10%, respectively. At the first visit, the younger children with greater hyperopic state exhibited more noticeable myopic shift, no significant difference was found in gender. Conclusions: The shift from hyperopia to myopia in preschool children is smooth, with -0.20D change on average per year. We suggest that an optometry screening should start at t3-year-old to track children’s refractive status. We recommend that preschool children whose SE changes more than -1.00 D per year go to the ophthalmology department for further examination. Our study also found that at the first visit, the younger the child is and the more positive initial SE is, the degree of shift of myopia is greater. Keywords: Refractive error, preschool myopia, myopia, risk factors, retrospective cohort studies